Kidney complications resulting from SARS-CoV-2 virus infection - Colli, Emillene de Holanda (2022)
It is known that Covid-19, a pathology discovered at the end of 2019, in the city of Wuhan, China, has spread in several countries, being characterized as a pandemic, has been causing several complications, the main one being the discomfort syndrome. acute respiratory disease (ARDS), but it can cause damage to other organs. Thus, the current study aims to evaluate the kidney injuries caused by Covid-19 and what are the main renal manifestations presented. A narrative literature review was carried out, anchored in the Google Scholar, ScientifEletronic Library Online (SciELO) and PubMED databases, using the descriptors: “covid-19”, “nephropathies”, “acute kidney injury”, “kidney damage”, “renal complications”, published in English and Portuguese during the year 2020 to 2022. 550 scientific productions were collected, 50 productions were selected, 30 of which matched the inclusion criteria after checking the abstracts, but only 20 were used after full reading of the contents. The analyzes suggest that the main kidney injuries caused are electrolyte disturbances, proteinuria, hematuria, metabolic acidosis, which lead to increased creatinine and decreased glomerular filtration rate, this is due to systemic inflammation and hypercytokinemia cascade (IL-6, IL-2, TNF-alpha, and IL-10) that result in systemic endothelial dysfunction and a hypercoagulable state that cause tubular injury in patients with acute renal syndrome.